Memperpanjang Kecerahan Cahaya Lampu TL (fluorescent) Dengan Menggunakan Metode Penyalaan Switching - Supriono, Supriono (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2009)
The tactic, that generally people to make tube lamp (fluorescent) brightly shines on area that has poor voltage regulation at peak load time, is applied of bigger ballast transformer than its rating. Unfortunately, the side effect results life of lamp to be shorter marked by falling of its brightness. At this time, fluorescent lamp applying as lighting is turned on day-and-night 24/7. It happens on home that light of sun can not enter its rooms. Turning on fluorescent lamp using switching method gives more benefit that is : it can be brighten under low voltage until 120 V, further more the life of fluorescent lamp is longer than ballast method when it turn on continuously. Fluorescent lamp rating 10 watt that is using 10 watt ballast transformer made in Guang Zhow only shines 5 days when it work day-and-night, on the other hand 10 watt fluorescent lamp from Phillips has durability as its long-life but its brightness decreases signed by increasing resistant of LDR from 2200 ohm to 2600 ohm after turned on along 60 days. Fluorescent lamp 20 watt made in Matsui and ballast transformer 20 watt made in Sinar have superiority as well as switching method that is the value of LDR resistant not change at 2000 ohm, although it had worked along 60 days without turned off.